FENOMENA HIJRAH ARTIS DALAM PERSPEKTIF PSIKOLOGI TRANSPERSONAL - Fitri Umami, Idail Uzmi; Sobri, Muhammad; Syazali, Muhammad (Jurnal El-Hikam, 2022)
Today, we can see in various media, especially on television, a lot of news about some artists who decided to change their appearance in a more religious direction, some decided to wear hijab and some let their beards grow, they changed their appearance not without reason and interesting things interesting enough we review the reason they emigrated. Some examples of artists who decided to migrate include Kartika Putri, Laudya Cintya Bela, Harry Moekti, Mike Lucock, Natalie Sarah and others. The average reason for them is a spiritual experience that they experience so as to create awareness in the heart. Departing from this problem, it is associated with one of the branches of the fourth school of psychology, transpersonal psychology. According to Davis, transpersonal psychology is between psychology and spiritual experience. hence from this it is necessary to examine the phenomenon of migrating artists with transpersonal psychology.